Intervensi Negara dalam Penyehatan Perusahaan Pengalaman Negara Sedang Berkembang - Suwarsono Muhammad (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This paper attempts to explain in detail the role of the state, especially in developing countries, to promote corporate recovery during the economic crisis period. In so doing, first, the paper illuminates several important reasons why the state has to intervene in the case of economic crisis. It seems that the whole process of corporate turnaround has to be initiated by the state and hence it is called state-led corporate restructuring. Second, the paper intents to explain three stages of corporate turnaround: restructuring preparation, financial sector restructuring, and corporate restructuring, followed by an explanation of corporate restructuring techniques usually used by the state. Finally, the paper shows how the state should exit from the market.Key words: state, intervention, recovery, crisis.